Glucosamine Interferes With Myelopoiesis and Enhances the Immunosuppressive Activity of Myeloid-Derived Suppressor Cells - Lin, Eric Chang-Yi; Chen, Shuoh-Wen; Chen, Luen-Kui; Lin, Ting-An; Wu, Yu-Xuan; Juan, Chi-Chang; Chang, Yuan-I (Frontiers in Nutrition, 2021)
Glucosamine (GlcN) is the most widely consumed dietary supplement and exhibits anti-inflammatory effects. However, the influence of GlcN on immune cell generation and function is largely unclear. In this study, GlcN was delivered into mice to examine its biological function in hematopoiesis. We found that GlcN promoted the production of immature myeloid cells, known as myeloid-derived suppressor cells (MDSCs), both in vivo and in vitro. Additionally, GlcN upregulated the expression of glucose transporter 1 in hematopoietic stem and progenitor cells (HSPCs), influenced HSPC functions, and downregulated key genes involved in myelopoiesis. Furthermore, GlcN increased the expression of arginase 1 and inducible nitric oxide synthase to produce high levels of reactive oxygen species, which was regulated by the STAT3 and ERK1/2 pathways, to increase the immunosuppressive ability of MDSCs. We revealed a novel role for GlcN in myelopoiesis and MDSC activity involving a potential link between GlcN and immune system, as well as the new therapeutic benefit.